Comparison of swab types & elution buffers for collection and analysis of intact cells to aid in deconvolution of complex DNA mixtures. (November 2022) - Canfield, Jeremy R.; Jollie, Melissa; Worst, Travis; Oechsle, Crystal
Abstract: Heightened sensitivity of forensic DNA techniques has led to an increased variety of samples tested, often yielding complex DNA mixtures, in turn making the interpretation of profiling results more complicated. Currently, there is no prescribed upstream laboratory method to separate complex DNA mixtures by their contributors; therefore, a method is needed that could reduce mixtures into their component parts. Various cell sorting applications have the potential to be this method, if intact cells can be reliably obtained from forensic samples. Here, the effects of elution buffer and swab substrate on the recovery of intact, human, white blood cells from dried blood samples were evaluated. Approximately 328, 000 cells per swab were deposited onto cotton, flocked, and dissolvable swabs. The whole-cell elution of the dried samples was evaluated with water, phosphate buffered saline, and AutoMACS® elution buffers. We demonstrate that AutoMACS® buffer is superior for the elution of intact cells, compared to phosphate buffered saline and water. When swab type was considered, the highest yield of intact cells resulted from flocked swabs, as opposed to cotton or dissolvable swabs. Highlights: The introduction of a swab substrate decreases recovery of intact cells. AutoMACS® buffer is more effective than water or PBS for recovery of intact cells. Flocked swabs outperform other swabs types in their ability to release intact cells. The use of cotton swabs for biological sample collection should be re-evaluated.